Navigating Post-Covid-19 Learning: Assessing Curriculum, Facilities, and Human Resource Developments and Challenges - Ruswandi, Bambang; Fatihunnada, Fatihunnada; Zulkifli, Dhea Urfina; Zainudeen, Musah Issa (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze learning development and the obstacles experienced by the Nahdlatul Ulama Islamic boarding school in Bekasi Regency after the COVID-19 pandemic, from curriculum, facilities, and human resources. This study uses a quantitative approach. The research subjects were students and caregivers from three NU Islamic boarding schools in the Bekasi district: Yapink, Nurul Huda Islamic Boarding School, and Indonesian Motivational Islamic Boarding School. The sampling method used in this research is Stratified Random Sampling and Systematic Random Sampling with proportional composition. The sample size was 320 students with sampling error = 0.05, proportion = 0.5, and the standard value of normal distribution at 5% level, z = 1.96. The test results concluded that the quality of student learning in the new average period was generally still relatively low. Educational barriers are a factor that makes the quality of student learning feel less than optimal. This is due to the impact of Covid-19 with the enactment of distance learning, the family economy is affected, and the increase in the price of health facilities, but from an institutional resilience and vulnerability standpoint, it is quite good.